INFLUENCE OF THE ADDITION OF PARAFFIN AND GRAPHITE ON ETHYLENE PROPHYLENE DIENE MONOMER (EPDM) FOR THERMAL ENERGY STORAGE - Pocut Nurul Alam; Isra Adelya Izzati; Rima Dhinta Dewi Astuti; Umi Qhanita Putri Swya; Teuku Muhammad Daffa Rihayat (Politeknik Negeri Lhokseumawe, 2023)
This study aims to determine the effect of the paraffin: graphite ratio on the thermal resistance of the Phase Change Material (PCM). PCM mixed with Ethylene Propylene Diene Monomer (EPDM) which has good compatibility with paraffins as a base polymer for preparing paraffin graphite composites. The samples was prepared by using heating method at 180oC for 20 minutes with a variation of the ratio 9:1 and 8:2 with mass ratios PCM70 : EPDM30, PCM80 : EPDM20, and PCM90 : EPDM10. Based on the results of tensile strength testing, thermal stability analysis and SEM. the maximum tensile strength is obtained at a mass ratio of 80% : 20% with a ratio of 9:1 which is 9.34 Mpa, has a thermal stability of 307.04oC at onset and Endset at a temperature of 399.50oC, However, there is an aggregate form that is agglomerate and has large pores, as well as a rough surface on the sample. While the results of the Morphology test using SEM, the best interaction between polymers with a mass ratio of 70%:30% at a ratio of 9:1, with a very well mixed surface, smooth, no lumps formed.Â Keywords: EPDM; Graphite;Paraffin;PCM;PolymersÂ